PENGARUH PEMBERIAN BUBUK DAUN KEMANGI DAN SUKU TERHADAP POPULASI Sitophilus zeamais DAN KUALITAS BENIH JAGUNG YANG DISIMPAN - Rahmawati, Fauziah; Solichah, Chimayatus (UNIVERSITAS PEMBANGUNAN NASIONAL ”VETERAN” YOGYAKARTA, 2025)
Damage to stored corn seeds due to the pest Sitophilus zeamais can be suppressed by control. One of alternative to pest control is using botanical pesticides with basil and breadfruit leaf powder. This study aims to determine the effect composition and type of leaf powder in suppressing of Sitophilus zeamais. The research was conducted in February to April 2024 at Plant Protection Laboratory, UPN